Design and Optimization of CdSe–CuSbSe2-Based Double-Junction Two-Terminal Tandem Solar Cells With VOC > 2.0 V and PCE Over 42% - Sheikh Noman Shiddique; Ahnaf Tahmid Abir; Md Jayed Hossain; Mainul Hossain; Jaker Hossain (International Journal of Photoenergy)
In this article, we demonstrate CdSe–CuSbSe2-based double junction two-terminal tandem solar cells simulated with SCAPS-1D. The highest performance of the tandem cell has been confirmed by optimizing the electrical and optical properties of the window, top absorber, CdSe (bandgap 1.7 eV), bottom absorber, CuSbSe2 (bandgap 1.08 eV), and back surface layers. In addition, the effect of different parameters such as thickness, doping, and defect density of different layers has been investigated in detail. With the optimized condition, the modeled CdSe–CuSbSe2 double-junction two-terminal tandem solar cell displays a noticeable efficiency of 42.64% with an open-circuit voltage of 2.09 V, short-circuit current density of 24.09 mA/cm2, and fill factor of 84.36%, respectively. These results are highly propitious for the construction of all-chalcogenide–based high-performance tandem photovoltaic cells in the future.